2013
DOI: 10.3390/s130404514
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Zenith Tropospheric Delays from BeiDou Navigation Satellite System Observations

Abstract: The GNSS derived Zenith Tropospheric Delay (ZTD) plays today a very critical role in meteorological study and weather forecasts, as ZTDs of thousands of GNSS stations are operationally assimilated into numerical weather prediction models. Recently, the Chinese BeiDou Navigation Satellite System (BDS) was officially announced to provide operational services around China and its neighborhood and it was demonstrated to be very promising for precise navigation and positioning. In this contribution, we concentrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…It has been demonstrated that BDS is capable of providing PNT service with an accuracy comparable to GPS (Ge et al 2012;Li et al 2015). Xu et al (2013) made an assessment on ZTD estimated from observations of a BDS local network with a time span of 4 days for the first time. Their comparison with GPS ZTD from IGS showed a bias and standard deviation of about 2 and 5 mm, respectively, being at the same level as the difference between GPS ZTD estimated by different software packages (Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that BDS is capable of providing PNT service with an accuracy comparable to GPS (Ge et al 2012;Li et al 2015). Xu et al (2013) made an assessment on ZTD estimated from observations of a BDS local network with a time span of 4 days for the first time. Their comparison with GPS ZTD from IGS showed a bias and standard deviation of about 2 and 5 mm, respectively, being at the same level as the difference between GPS ZTD estimated by different software packages (Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2013) made an assessment on ZTD estimated from observations of a BDS local network with a time span of 4 days for the first time. Their comparison with GPS ZTD from IGS showed a bias and standard deviation of about 2 and 5 mm, respectively, being at the same level as the difference between GPS ZTD estimated by different software packages (Xu et al 2013). According to the results from BeiDou Experiment Tracking Network (BETN), Li et al (2014a) indicated that the PWV estimated from the BDS PPP can achieve similar precision as GPS-derived PWV.…”
Section: Introductionmentioning
confidence: 99%
“…PPP Client. Aside from the above mentioned network, a regional network comprising six different stations (Xu et al, 2013) equipped with the same UNICORE receivers and antenna were also employed as user stations for the tests of various precise point positioning modes. The inter-station distance is about 150 km on average.…”
Section: Introduction Since 1985mentioning
confidence: 99%
“…GNSS can be used to estimate the zenith tropospheric delay [8] and to estimate precipitable water vapor content [9]. GNSS signals travel through the atmosphere, and so it may be asked whether GNSS signals are refracted by the atmospheric particulate matters or not.…”
Section: Introductionmentioning
confidence: 99%